Design Optimization of Pressurized Gyration Technology: Orifice Height Level Effects on Production Rate and Fiber Morphology - Ahmed Alneyadi; Angelo Delbusso; Anthony Harker; Mohan Edirisinghe (Macromolecular Materials and Engineering, 2025)
Abstract Electrospinning and pressurized gyration are two widely adopted methods for polymeric fiber production, valued for their simplicity, versatility, and relatively low environmental impact. Despite its advantages, electrospinning has notable limitations, including low production efficiency and significant safety concerns. Pressurized gyration, however, offers greater productivity and a safer, more sustainable process, making it an excellent candidate for industrial scaling. To fully realize this potential, optimizing the pressurized gyration process is essential for enhancing efficiency and achieving sustainable large‐scale fiber production. In this study, the effects of vessel orifice height on the production rate and fiber morphology in pressurized gyration are explored. A series of experiments is conducted using a 15 wt.% polycaprolactone (PCL) solution, with vessels of identical diameter but differing orifice heights 7.5, 15, and 22.5 mm tested under pressures of 0, 0.1, 0.2, and 0.3 MPa, all at a constant rotational speed of 13 000 rpm. The 7.5 mm orifice height demonstrates the highest production rate under pressure while increasing orifice height led to finer fiber diameters, better alignment, and smaller beads. These findings underscore the importance of optimizing vessel design, along with process and solution parameters, for scaling up pressurized gyration fiber manufacturing to meet industrial demands.